PENGARUH CAR, NIM, LDR, NPL DAN BOPO TERHADAP PERUBAHAN LABA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2013-2016 - Tuti Rahmadani (Universitas Islam Malang, 2017)
ABSTRACTThis research was conducted to test the effect of the indicators ratio of the healthof banks to profit growth. the indicators ratio of the health of banks examined is thevariable CAR (Capital Adequacy Ratio), NIM (Net Interest Margin), LDR ( Loan toDeposit Ratio, NPL ( Non Perfoming Loan), and BOPO ( Operational Cost OperationalRevenue),), toward provit growth. the data used was the publication of the annual reportby banking companies enlisted in BEI in 2013 - 2016. the population in this researchwas the all banking companies enlisted in BEI in 2013 - 2016.The sampling technique used was by purposive sampling with the sample of 32companies. the technique of analyzing the data was multiple linier regression andhypothesis test was by t-statistic to test the coefficient of partial regression and fstatistic. it consisted of normality test, the classical assumption test was also conducted,multiconearity test, heteroxidasity test the auto correlation test. from the partialhypothesis (t test), it showed variabel BOPO affect positive significantly toward theprovit growth. And it showed variabel of CAR, NIM, LDR, and NPL did not affectsignificantly toward the provit growth.KEYWORD : CAR, NIM, LDR, NPL, BOPO, PROVIT GROWTH.